Risk factors for Hickman-Broviac catheter complications: An experience from a Tunisian hospital - Manel Kammoun; Anouar Jarraya; Hend Ketata; Saloua Ammar; Mohamed Zouari; Chiraz Regaieg; Nadia Hentati; Mahdi Ben Dhaou; Riadh Mhiri (EL-Med-Pub, 2022)
Background: Hickman-Broviac catheters have improved the care of young children needing frequent and prolonged venous access, but at the same times it has substantial morbidity, particularly in a resource-constrained setup. Our study aims to describe the experience of a Tunisian hospital and investigate the main risk factors for complications. Methods: In this study, we included all the neonates and infants who underwent Broviac catheter insertion in the pediatric surgery department. The patients were divided into 2 groups according to the presence of complications. We compared these two groups and univariate logistic regression analyses were used to determine the risk factors for complications. Results: Forty-three children were included in the study. The incidence of complicated catheters was 60.4%. The following factors were significantly associated with an increased risk of complications: age 6 months [OR 3.5, 95% CI: 0.6-19.3], weight 6 kg [OR 1.54, 95% CI: 0.46-5.2], emergency circumstances [OR 1.62, 95% CI: 0.8-5.4], and antibiotic-therapy as an indication for Broviac catheter insertion [OR 1.8, 95% CI: 0.5-6.2]. Conclusion: Complications seem to be more frequent in patients younger than 6 months and those with a weight of less than 6Kg. To reduce the morbidity related to the catheters, the indications should be carefully chosen.